Karkumorsian - Miljoonasade (yhtye); Aho, Susan; Hovi, Jarmo; Aholainen, Tomi; Kaasinen, Mari; Kallio, Matti; Kantelinen, Karoliina; Laaksonen, Ari; Nurro, Matti; Paleface; Salo, Heikki; Värttinä (yhtye) (Sateen Ääni Oy, 2019)
12 kappaletta.
Keywords: Miljoonasade (yhtye) : albumit